Gender equity: a critical issue for women's advancement to senior management postions in South African higher education - Mkhonza, Mokgadi Johanna (University of the Free State, 2004)
English: The number of women entering the workforce has escalated over the past thirty years. However, in terms of employment and promotion, women often face greater handicaps than men in that women continue to compete in the workforce on an unequal footing with men, and as a result continue to experience unequal labour market outcomes. In higher education, progress to elevated levels of employment and occupations seems to be much more problematic for women than for men. Although the number of women in the academe has increased, women are still concentrated in lower and middle management and in unskilled jobs whilst forming a minority in the most senior positions. This situation prevails both developed as well as developing countries. The main objective of this study was to analyse the position of women in management and their experiences in higher education institutions in the South African context. Furthermore, this study also reported on the obstacles that these women may have had to face in their attempt to gain entry into the higher echelons of these institutions. The absence of career paths to these positions further exacerbates the situation. This study therefore focused on amplifying the existing body of knowledge on the experiences of women in management positions in higher education and the barriers they face with regard to their advancement to senior positions, as well as possible mechanisms to enhance their empowerment. From the literature review it became clear that societies often perceive the differences between men and women as natural; but masculinity and femininity are hierarchical contrasts, and categories associated with femininity are perceived as inferior and subordinate whilst categories associated with masculinity are perceived as dominant. Through socialisation, this socially constructed segregation between men and women, and the roles attributed to each sex, are inculcated by the family and reinforced by other socialisation agents such as schools, peers, religion and the media. Children therefore learn from infancy about the relationship between biological sex and social roles. Prior to the industrial revolution, family and work life were intertwined for most people. The division of labour only came into being with the advent of industrialisation. Men started engaging in jobs outside the home and women increasingly assumed responsibility for family life, with most of them destined for hard physical labour dominated by patriarchal systems. These attitudes continue to persist. The division of labour means that, in almost all the economies, women are concentrated at the lower end of the labour market. In South Africa, though, as a result of the heritage that racism brought to this country, black women – in contrast to their white counterparts who were discriminated upon just in terms of gender – suffered discrimination based on gender, race and class. Recently the traditional female roles have been showing signs of change – a process that has been accelerated in South Africa as a result of the country’s new constitution, as well as other legislative gender machinery. These legislative frameworks imply that the nontraditional work opportunities for women have increased in all sectors of employment and in particular in the higher education sector. Despite this, however, women continue to be underrepresented in decision-making positions in the workplace. Furthermore, women are still subjected to the strain caused by gender stereotyping as a result of patriarchal beliefs. Women seeking equity in the education management world are often confronted by stereotypical gender views, which negatively impact on their performance levels and productivity There are very low numbers of women in executive management positions in higher education. Women are underrepresented at the ranks of vice-chancellor, deputy vicechancellor, dean and head of school. Higher education institutions are dominated by male leadership; those few women who manage to reach the top often report isolation and lack of support and recognition from their male colleagues. Most people believe that by closing the leadership gap between the two sexes, institutions will become more centred on persons and processes. But the problem is that leadership has traditionally been studied using male norms as the standard for behaviours. Women have adopted male standards of success to better fit into male-dominated hierarchical structures and systems. Moreover, women in these positions owe their commitment to the norms and values of the dominant male society. A qualitative investigation was the dominant method used and thus formed the core of this study, with the quantitative investigation being the alternative, less-dominant method. Thirteen females in management positions were selected from six universities in South Africa. The respondents came from diverse cultures and backgrounds. The Leadership Practices Inventory (LPI) questionnaire was used to determine whether the leadership styles employed by women in higher education institutions met the standard as set by these institutions. The results of the LPI indicated that although society does not associate women with leadership, women’s scores on the LPI items were rated moderate to high. Thereafter, structured and semi-structured in-depth interviews were conducted with the 13 female managers to ascertain their opinions and perceptions with regard to their advancement to senior management positions and their experiences once they had attained these positions. During the empirical investigation the respondents attested to their experiences of direct gender discrimination in promotion and appointment, as well as patriarchy and sexual and emotional harassment. Respondents also revealed how these practices were impacting on their performance as managers. In addition, family arrangements can be quite unequal in terms of sharing the burden of housework and childcare. In many societies, it is quite commonly taken for granted that while men will naturally work outside the home, women may do so if and only if they can combine it with various inescapable and unequally shared household duties. The participants’ responses to a great extent correlated with the literature in revealing solutions for curbing the problems related to women’s under-representation in management in higher education. Women need to form groups and women’s movements, take an active stance, and speak in one voice against this inhumanity. Society’s attitude and behaviour towards women also need to change. Both sexes should strive towards achieving equity and equality. Education institutions can also play a vital role in this regard – from promoting gender sensitivity to implementing programmes aimed at changing societal views on gender and recruiting more women into the system, as well as changing the institutional culture to make it more accommodating to women. In the final chapter of the study, the researcher formed a synthesis of the findings from the literature overview, the qualitative study and the results of the quantitative investigation. The report indicated how female managers in higher education were influenced by stereotyping and the institutional environment that is not conducive to women’s advancement to decision-making and authority positions. Recommendations for the enhancement of women’s empowerment in order to allow them to advance to management positions in higher education were provided at the end of the final chapter. From the recommendations, it is clear that strategies need to be put in place to increase the number of women in senior management positions. A prerequisite to meet this challenge is a change in the attitude of society, which very often still regards women as inferior to men, to allow every citizen to work towards the realisation that women’s rights are human rights, and that South Africa can never be a true democracy until women, too, can claim full enjoyment of all the human rights enshrined in the constitution.

Afrikaans: Die hoeveelheid vroue wat die arbeidsmark betree het oor die afgelope dertig jaar betree het, geëskaleer. In terme van werkverskaffing en bevordering ervaar vroue egter groter struikelblokke as mans. Vroue kompeteer steeds op ‘n ongelyke voet met mans en as gevolg daarvan ervaar hulle steeds ongelykhede in die arbeidsmark. In hoër onderwys is bevordering tot hoër vlakke van werkverskaffing en beroepe meer problematies vir dames as vir mans. Ten spyte van die feit dat die getal vroue in die akademie verhoog het, bevind die meeste vroue hulle steeds op middelbestuursvlak en in posisies wat werk met minder vaardighede vereis. In senior posisies is die minderheid dan gevolglik ook vroue. Hierdie situasie kom in beide ontwikkelde en ontwikkelende lande voor. Die hoofdoel van hierdie studie was om die posisie van die vrou op bestuursvlak, asook hulle ondervinding in hoër onderwys in Suid Afrikaanse konteks, te analiseer. Hierdie studie rapporteer ook verder aangaande die struikelblokke wat vroue sou ondervind in hulle poging om toegang te verkry tot die hoër vlakke van sodanige instansies. Hierdie studie fokus gevolglik op die ondervinding van vroue in bestuursposisies in hoër onderwys asook die hindernisse met betrekking tot hulle bevordering na senior posisies, met die oog op die daarstelling van moontlike meganismes om sodoende die probleme wat daarmee gepaard gaan te oorkom en bemagtiging te bevorder. Vanuit die literatuuroorsig is dit duidelik dat die gemeenskap gereeld die verskille tussen mans en vroue as natuurlik ervaar, hoewel manlikheid en vroulikheid as hiërargies kontrasterend beskou word. Dit word ook verder ervaar dat kategorieë wat met vroulikheid geassosieer word ondergeskik aan manlike kategorieë is wat as dominant ervaar word. Deur sosialisering word hierdie sosiaal gekonstrueerde segregasie tussen mans en vroue, asook die rolle wat aan elke geslag toegeken word, verder deur sosiale agente soos skole, portuurgroep, godsdiens en die media versterk. Kinders leer dus van jongs af wat die verwantskap tussen geslag en sosiale rolle is. Voor die industriële revolusie was die familie en die lewe van werke met mekaar verweef. Die eerste verdeling van arbeid het met die koms van industrialisasie begin realiseer. Mans het meer by werk buite die huis betrokke geraak, terwyl vroue al hoe meer verantwoordelikheid vir die familie aanvaar het, wat harde fisiese arbeid beteken het, tewyl hulle deur patriargale sisteme oorheers is. Hierdie patriargale stelsels het egter bly voortbestaan en die verdeling van arbeid het beteken dat vrouens op die laer vlakke van die arbeidsmark gekonsentreer het. In Suid Afrika egter, as gevolg van die nalatenskap van rassisme, het swart vroue, in kontras met hulle wit eweknieë en teen wie gediskrimineer is slegs in terme van geslag, verdere diskriminasie wat op geslag, ras en klas gebaseer is, ondervind. Onlangs het die tradisionele rolle van vroue tekens van verandering begin toon – ‘n proses wat in Suid Afrika as gevolg van die land se nuwe grondwet asook die nuwe wetgewing aangaande ras versnel het. Hierdie wetgewingsraamwerk impliseer dat die nie-tradisionele werksgeleenthede vir vroue in alle sektore van werkverskaffing vermeerder het, gevolklik ook in die hoër onderwyssektor. Ongeag laasgenoemde tendens, is vroue steeds onderverteenwoordig in besluitnemingsposisies in die werkplek. Vroue is steeds ook onderworpe aan bykomende druk wat deur geslagstereotipering as gevolg van patriargie, veroorsaak word. Vroue wat gelykheid in die opvoedkundige bestuurswêreld nastreef, word soms gekonfronteer met stereotipiese geslagsmenings wat dan weer ‘n negatiewe inpak op hul prestasievlakke en produktiwiteit het. Daar is min vroue in uitvoerende bestuursposisies in die hoër onderwys sektor, veral in die posisies van vise-kanseliers, adjunk vise-kanseliers, dekane en hoofde van skole. Hoër onderwysinrigtings word steeds deur manlike leierskap oorheers. Die paar vroue wat wel hierdie sport bereik, ondervind isolering en gebrek aan ondersteuning en erkenning deur hulle manlike kollegas. Kundiges is van mening dat, deur die leierskapsgaping tussen die twee geslagte uit die weg te ruim, die instellings meer persoon- en prosesgesentreerd sal raak. Die probleem is egter dat leierskap wat in die verlede bestudeer is, manlike norme as standaard van gedrag gebruik het. Vroue het manlike standaarde van sukses aanvaar om sodoende beter in te pas in manlik oorheersde hiërargiese strukture en sisteme wat daartoe gelei het dat vroue hulle kompromiteer tot die norme en waardes van ‘n dominante manlike samelewing. ‘n Kwalitatiewe ondersoek was die dominante metode wat in hierdie ondersoek gebruik is en ‘n kwantitatiwe ondersoek as alternatiewe minder dominante metode. Dertien vroue in bestuursposisies uit ses universiteite in Suid-Afrika gekies is. Die respondente het uit verskillende kulture en agtergronde gekom. Die Leadership Practices Inventory (LPI) vraelys is gebruik om vas te stel of die leierskapstyle van vroue in hoër opvoedkundige inrigtings ooreenstem wat van die goeie leiers verwag word is. Die uitslae van die LPI het aandui dat, alhoewel die samelewing nie vroue met leierskap assosieeer nie, vroue oor die nodige eienskappe beskik. Hierna is gestruktureerde en semi-gestruktureerde in-diepte onderhoude met die dertien vroulike bestuurders gevoer om hulle menings en persepsies met betrekking tot hulle bevordering tot senior bestuursposisies en hulle ervarings in hierdie verband vas te stel. Gedurende die kwalitatiewe empiriese ondersoek het die respondente se ondervinding van direkte geslagsdiskriminasie in aanstellings en bevorderings asook patriargale, seksuele en emosionele teistering na vore gekom. Die respondente het ook openbaar hoe hierdie praktyke ‘n inpak op hulle werkverrigting as bestuurders het. Reëlings binne die gesinsopset kan ook baie oneweredig in terme van die lading van huiswerk en kinders se sorg versprei wees. In baie samelewings word dit algemeen aanvaar dat dit natuurlik is dat die man buite die huis werk en dat vroue slegs mag werk as hulle dit kan kombineer met hul onoorkomlike en oneweredig verdeelde huishoudelike pligte. Die deelnemers se response het grotendeels gekorreleer met die bevindinge uit die literatuur en het bepaalde oplossings vir vroue se probleme in bestuursposte in die hoër onderwys, die lig laat sien. Sodanige oplossings sluit in groepvorming en standpuntinname teen hierdie ongelykhede. Die gemeenskap se gedrag en houding teenoor vroue sal ook moet verander, en beide geslagte sal na billikheid en gelykheid moet streef. Opvoedkundige inrigtings kan ‘n kragtige rol speel in hierdie verband, van propagering van geslagsensitiwiteit tot implementering van sodanige programme. Die programme behoort daarop gerig wees om sosiale menings oor geslag te verander, vroue vir die sisteem te werf en om die institusionele kultuur te verander sodat dit meer akkommoderend ten opsigte van vroue sal wees. In die finale hoofstuk van die navorsing vorm die navorser ‘n sintese vanuit die literatuuroorsig, die kwalitatiewe navorsing asook die resultate van die kwantitatiewe ondersoek. Die verslag dui aan hoe vroulike bestuurders in hoër onderwys deur stereotipering beïnvloed word en dat die institusionele omgewing nie tot die vroue se bevordering tot besluitnemingsprosesse en magsposisies bydra nie. Aanbevelings ten opsigte van die bemagtiging van vroue, sodat hulle in staat gestel kan word om tot bestuursposisies in hoër onderwys bevorder te word, word aan die einde van die finale hoofstuk gedoen. Vanuit die aanbevelings blyk dit duidelik dat dit noodsaaklik is om strategieë te ontwikkel om te verseker dat daar ‘n toename in die hoeveelheid vroue in senior bestuursposisies is. ‘n Voorvereiste tot hierdie uitdaging is die verandering van die houdings van die gemeenskap, naamlik dat vroue volwaardige landsburgers is en dat die regte van ‘n volwaardige demokratiese land wees alvorens vroue nie volledig kan deel in alle basiese menseregte van die grondwet nie.
Keywords: Women in higher education -- South Africa; Gender identity in education; Discrimination in higher education -- South Africa; Women college administrators -- Selection and appointment -- South Africa; Educational leadership; Thesis (Ph.D. (Comparative Education and Education Management))--University of the Free State, 2004